Design, Synthesis, In-Silico Study of Novel Benzofuran Thiazolyl Hydrazones as Anticancer Agents Targeting EGFR Kinase - Shinde, Sonali Sandeep; Kilbile, Jaydeo Tirthraj; Bhusari, Sachin Shivling; Wakte, Pravin Shridhar (Universitas Gadjah Mada, 2025)
In the current investigation, a series of new benzofuran-thiazolyl hydrazones 5(a–h) were synthesized, characterized, and tested for anticancer activity against selected cancer cell lines, including A549, MCF-7, and DU-145, using MTT and EGFR enzymatic assays. The synthesized compounds 5g and 5h showed considerable anticancer activity, with IC₅₀ values ranging from 9.05 to 18.09 μM and 12.03 to 13.09 μM, respectively. Doxorubicin and osimertinib were used as the standard drugs for comparison of activity. Compounds 5g and 5h also showed significant antioxidant activity as measured by the DPPH method. The molecular docking investigation was conducted against the EGFR (PDB: 1M17) to learn about the interactions of synthesized compounds with binding pockets. Furthermore, an ADME research and molecular dynamics simulation study was conducted to provide insight into drug-likeness and conformational stability. The results show a good match between reported anticancer effects and computational analyses. Compounds 5g and 5h exhibited significant cytotoxicity against lung, breast, and prostate cancer cell lines. These findings underscore the potential of benzofuran-thiazolyl hydrazone derivatives as promising candidates for the development of novel anticancer therapeutics.